Penguatan Karakter Melalui Seni Bela Diri Pencak Silat Kuntau Pada Masyarakat Kalimantan Selatan, Indonesia - Ruswinarsih, Sigit; Apriati, Yuli; Malihah, Elly (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
The symptoms of the weakening of the immoral behavior of the younger generation deserve more and more attention. The problem is how to develop character education based on local wisdom as a solution to this problem? The martial art of pencak silat is one of the local wisdoms of the Indonesian nation in the form of a series of methods of defending oneself from various physical attacks from outside oneself. Pencak silat kuntau is an alternative program to strengthen community character. This study explores the local wisdom values of kuntau martial arts and analyzes the practice of kuntau martial arts in order to strengthen the character of the fighters. Articles from research using a phenomenological approach obtain data through observation, in-depth interviews and documentation related to the learning process of martial arts. It was found that learning in the form of kuntau martial arts training contains character values, at least in the form of responsible and peace-loving behavior. The character of a fighter is formed through exercises, internal and external competitions, interactions before, during and after training and competition, as well as the example of the teacher (trainer). Based on the content of its noble values, kuntau martial art can be disseminated as a medium for strengthening character in society and schools.